Visible Minorities under the Canadian Employment Equity Act, 1987-1999 - Jain, Harish; Lawler, John (Relations industrielles / Industrial Relations, 2004)
This study focuses on the effectiveness of the federal Employment Equity Act (EEA). We assess the EEA with regard to visible minority (VM) employees using quantitative data from employer reports published under the provisions of the EEA and the Canadian Census. Data in this study cover the period 1987 to 1999. We find that large companies, and larger employment groups within companies, have higher levels of employment equity attainment. There are also considerable variations in employment equity attainment across industrial sectors, across provinces and across occupations. Overall, there has been general improvement in employment equity (EE) attainment over time. However, visible minorities continue to be disadvantaged in management, sales and service and technical positions. Several policy implications are drawn from these findings.